Implementing a regional standardized BK polyomavirus screening protocol across eleven transplant centres. (28th October 2021) - Rogers, Ralph; Bodziak, Kenneth; Cheema, Faiqa; Chobanian, Michael; Ebcioglu, Zeynep; Gabardi, Steven; Ghai, Sandeep; Gilligan, Hannah; Gohh, Reginald; Goyal, Nitender; Kavalam, George; Mehri, Basma; et al.
Summary: BK polyomavirus (BKPyV) reactivation is regularly monitored after kidney transplant to prevent progression to BK associated nephropathy (BKAN). The New England BK Consortium, made up of 12 transplant centres in the northeastern United States, conducted a quality improvement project to examine adherence to an agreed upon protocol for BKPyV screening for kidney transplants performed in calendar years 2016–2017. In a total of 1047 kidney transplant recipients (KTR) from 11 transplant centres, 204 (19%) had BKPyV infection, defined as detection of BKPyV in plasma, with 41 (4%) KTR progressing to BKAN, defined by either evidence on biopsy tissues or as determined by treating nephrologists. BKPyV infection was treated with reduction of immune suppressants (RIS) in >70% of the patients in all but two centres. There was no graft loss because of BKAN during the two‐year follow‐up. There were nine cases of post‐RIS acute rejection detected during this same period. Adherence to the protocol was low with 54% at 12 months and 38% at 24 months, reflecting challenges of managing transplant patients at all centres. The adherence rate was positively correlated to increased detection of BKPyV infection and was unexpectedly positively correlated to an increase in diagnosis of BKAN. Abstract : A BK polyomavirus (BKPyV) screening protocol was implemented across 11 transplant centers. Adherence to the screening protocol was low, but was positively correlated with both an increase in the detection of BKPyV infection as well as an unexpected increase in the diagnosis of BKPyV associated nephropathy.